Yerel olmayan sınır ve integral ek koşulları altında bir parabolik denklem için ters katsayı problemi - Korkmaz, Emrah (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2016)
Bu tez çalışması ikinci tür yerel olmayan sınır ve integral ek koşulları altında bir parabolik problem için bir katsayı belirleme ters problemine adanmıştır. Bu problemde parabolik denklemin çözümü ile beraber yalnızca zamana bağlı ısı kapasitesi katsayısının belirlenmesi ele alınmıştır. Ters problemin çözümünün varlığı ve tekliği Banach sabit nokta teoreminden yararlanılarak gösterilmiştir. Ayrıca çözümün giriş verilerine bağlı Lipschitz sürekliği de incelenmiştir.

This thesis is devoted to, an inverse problems of determination of coefficients in the parabolic problems with second kind nonlocal boundary and integral overdetermination conditions are considered. In this problem, the simultaneously determination of the solution of heat equation and the time-dependent coefficient of heat capacity is considered. The existence and uniqueness of solution of the problem is proved by using the Banach fixed point theorem. However, Lipschitz Continuous upon the data of solution is also studied.
An inverse coefficient problem for a parabolic equation in the case of nonlocal boundary and overdetermination conditions
Keywords: Matematik; Mathematics